(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is devoted to the gender problem and labor protection for working women. Compared to men, working women make up 40%. The article presents statistical studies on the number of working years in various countries of the world. It also notes the labor activity of women in Uzbekistan, their role in science The article is devoted to the gender problem and labor protection for working women. Compared to men, working women make up 40%. The article presents statistical studies on the number of working years in various countries of the world. It also notes the labor activity of women in Uzbekistan, their role in science.